Scientific dissertation on territorial sustainability and the environment - Sotelo Pérez, Ignacio (Observatorio Medioambiental, 2020)
In this research, an analysis of the relationships between urbanism vs. rural environment, which shows the consumption of natural resources in Spain, in the context of sustainability in its triple economic, ecological and social dimension. In this way, and, in order to know and assess the incidence of the processes emanating from urban growth in Spain, which occurred in recent decades, on the aforementioned consumption of natural resources, throughout the study it is shown, in detail, the relevance that the legislative application of laws, plans, programs and projects has had and continues to have, from the standards, both of urban growth itself and of Spanish urban centers, as well as of the environmental impact produced by them. Likewise, the activities that have been developed and are currently being developed are analyzed in order to manage the demand for natural resources in urban and rural areas, especially, making reference to saving and efficiency measures, as well as well as the set of uses of unconventional resources, such as rainwater or treated wastewater.
Keywords: Environment; territorial sustainability; legislation; town planning; rural environment; Spain.